2014
DOI: 10.1186/1476-511x-13-183
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile abnormalities seen in T2DM patients in primary healthcare in Turkey: a cross-sectional study

Abstract: BackgroundDiabetes is characterized by chronic hyperglycemia and disturbances of carbohydrate, lipid and protein metabolism. We aimed to research association between serum lipid profile and blood glucose, hypothesizing that early detection and treatment of lipid abnormalities can minimize the risk for atherogenic cardiovascular disorder and cerebrovascular accident in patients with type 2 diabetes mellitus.MethodsFasting blood glucose (FBG), total cholesterol (TC), high density lipoprotein (HDL), low density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
100
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 35 publications
19
100
2
3
Order By: Relevance
“…It supports the previous data regarding the use of HbA1c as a potential biomarker of CHD risk [16]. The results are in agreement with previous studies that found a similar association between glycemic control and cardiovascular risk predicted by lipid profiles [16,29]. High-risk group had a higher HbA1c value (9.18) than low risk group (8.84).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It supports the previous data regarding the use of HbA1c as a potential biomarker of CHD risk [16]. The results are in agreement with previous studies that found a similar association between glycemic control and cardiovascular risk predicted by lipid profiles [16,29]. High-risk group had a higher HbA1c value (9.18) than low risk group (8.84).…”
Section: Discussionsupporting
confidence: 83%
“…Reduced HDL was observed in 25% patients. These results are supported by the previous studies that demonstrated lipid abnormalities in diabetes patients [27,19,29,16]. As shown in table 2, TC and LDL values were higher in the highrisk category than low/medium risk category although the difference was not statistically significant (p = 0.42).…”
Section: Discussionsupporting
confidence: 80%
“…Lipid profile and diabetes have been shown to be the important predictors for metabolic disturbances including dyslipidemia, hypertension, and cardiovascular diseases [7]. The abnormalities of Carbohydrate metabolism observed in GDM may lead to affect other metabolism also especially lipid metabolism [8].…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is a metabolic abnormality that is frequently associated with diabetes mellitus and both of them play important predictors that can progress to coronary artery disease (CAD) and may even be a prerequisite for CAD, occurring before other major risk factors come into play. [18].…”
Section: Discussion:-mentioning
confidence: 99%